Career development and counseling : putting theory and research to work - Brown, Steven D. (Steven Douglas), 1947-; Lent, Robert W. (Robert William), 1953- (Hoboken, N.J. : Wiley, 2013)
'Career Development and Counseling, Second Editionfocuses on scientifically based career theories and practices, including those derived from research in other disciplines. Driven by the latest empirical and practical evidence, this text offers the most in-depth, far-reaching, and comprehensive career development and counseling resource available. The Second Edition includes new chapters on gender, race/ethnicity, social class and poverty, sexual minority identity, disability status, personality, and relational factors'--Provided by publisher.
Includes bibliographical references and indexes.
Keywords: Career development; Vocational guidance; Counseling